A Vibrant but Transparent Visual Language: A Re-Evaluation of Breakfast Cereal Packaging Design, Marketing Methods, and Decision-Making - Pasquale, Madison Renee (Curtin University, 2023)
Packaging design is a communication tool. Brands utilize it to convey their identity (Söderlund et al. 2017) and product attributes to consumers. Consumers employ it as an information source (Wyrwa and Barska 2017) at the purchase-point (Ku and Chen 2021). This research holistically examines breakfast cereal packaging design to understand brand communication and the impact on consumer behaviour and decision-making to identify improvements that can guide and facilitate healthy, informed decision-making.